Draft Annual Plan 2003-04 Volume-I Planning, Statistics and Science and Technology Department - Planning Commission (Planning Commission, 2003)
The outlay for the Annual Plan 2003-04 is Rs.9127.52 crores. This represents an increase of 6% over the budgetted outlay of Rs.8610.61 crores in 2002-03 and forms 21% of the Tenth Plan outlay of Rs.43558.22 crores. The District Plan size for Annual Plan 2003-04 has been proposed at Rs.668.08 crores. The outlay proposed for Externally Aided Projects in Annual Plan 2003-04 is Rs. 1537.62 crores. Under the Special Component Plan Rs.642.50 crores have been earmarked for the welfare of the Scheduled Castes and Rs. 128.90 crores for the Scheduled Tribes under the Tribal Sub Plan.
Planning, Statistics and Science and Technology Department